Business-Industry Collaboration in Developing Waqf Deposit Prototypes and SOPs in Islamic Financial Institution - Yaser Syamlan Taufik; Asnan Purba (Tazkia Islamic Finance and Business Review, 2025)
Keywords: Wakaf Deposit, Islamic Finance, Risk Management, Participatory Action Research, Islamic Financial Institutions, Waqf Core Principles, Financial Innovation